On Patient Well-being and Professional Authority - Solomon, Mildred Z. (The Hastings Center report, 2017)
Two papers in this issue address the limits of surrogates’ authority when making life-and-death decisions for dying family members or friends. Using palliative sedation as an example, Jeffrey Berger offers a conceptual argument for bounding surrogate authority. Since freedom from pain is an essential interest, when imminently dying, cognitively incapacitated patients are in duress and their symptoms are not manageable in any other way, clinicians should be free to offer palliative sedation without surrogate consent, although assent should be sought and every effort made to work with surrogates as harmoniously as possible. Ellen Robinson and her colleagues report on the implementation of a policy at Massachusetts General Hospital that supports do-not-resuscitate orders when cardiopulmonary resuscitation is likely to be ineffective or harmful, even if surrogates disagree. The “Doing No Harm” policy at MGH allows for what MGH calls a “medically indicated DNR” and what in some other places is called “a unilateral DNR”—the writing of an order not to provide cardiopulmonary resuscitation, regardless of surrogate disapproval. These kinds of DNR policies have emerged in some hospitals across the country and for much the same reason that Berger provides in his argument regarding palliative sedation. I support the reasoning and the policies in both the Berger and Robinson papers. However, as the authors would most likely agree, the problems they aim to remedy are not simply about the scope of surrogate and professional authority. They are also symptoms of inattention to professional obligations and system failures.